FAULT SEALING ANALYSIS AT MIDDLE STRATIGRAPHIC INTERVAL, BRAVO FIELD, KUTAI BASIN, EAST KALIMANTAN - ARIFIN SUWITO, ZAINAL
Bravo field is a faulted anticline trap which was controlled by 4 extensional faults which forming a graben system consists of EF-1 fault (eastern part of graben), WF-1 fault (western part of graben), and 2 antithetic fault of central graben system are CF-1 and CF-2 faults. The objective of this study is to identify the distribution of fault sealing capacity for those 4 main faults at Middle interval by using static method of SGR (shale gouge ratio) and the other fault sealing capacity parameters such as fault zone permeability (Kf) and threshold pressure. Fault sealing cut off was defined based on integrated reservoir connectivity analysis by using parameter of pressure, production and fluid contact evolution. Significant mud losses parameter and a depleted pressure without any production from wells penetrated faults were used as a calibration of those sealing cut off definition. Fault seal behaviour at Bravo field is predominantly controlled by facies distribution than throw value. Reservoir juxtaposition to shale normally will be sealed, while reservoir juxtaposition could be leaked or sealed. The result of study showing any changing orientation on sealing cut off as follows: - In lateral orientation, the western faults has higher SGR sealing cut off (higher chance to be leaked) compared to eastern faults. This orientation is related to sediment distribution which is fining orientation toward distal part. - In vertical orientation, it is indicated that upper interval tend to be leaked compared to lower interval. This is related to regressive sequence pattern along Middle interval study which is indicated of paleogeographic changing from prodelta-delta front environment toward a delta plain until a fluvial system. The result of study could be used as an input correction on reservoir modelling, reservoir management and strategy of Bravo field development in future.